(untitled) (Indian Journal of Animal Production and Management, 2024)
Today, small-scale poultry farming plays a significant role in meeting the global demand for poultry products. It is no secret that small-scale farmers’ profitability is strongly impacted by the effectiveness of egg incubation, a key stage in poultry production. Brood quality and hatchability are strongly affected by temperature, humidity, ventilation, and turning during the incubation stage. Considering all these factors, designing an accurate, affordable, and effective incubator has become a challenging task. Incubation systems are now widely used by large-scale chicken farmers but small-scale poultry producers do not employ them as frequently. The lack of finance and technology has hindered the efforts of numerous small-scale chicken farmers who have expressed interest in employing incubation systems. Taking all these factors into consideration, this research has developed a highly efficient and cost-effective egg incubator that satisfies the special needs of small scale poultry farmers to solve those problems. The results of this study showed remarkable efficiency of up to 90% with a high yield of eggs stored in the compact incubator by maintaining optimal conditions of temperature, humidity, ventilation, egg turning, and other critical factors. In addition, this creative approach can contribute more to the growth of small-scale farmers’ economy and to meet the global demand for poultry products.